Penerapan Lesson Study untuk Meningkatkan Performansi Mengajar Dosen dalam Perkuliahan Nahwu Di Kelas - Khasairi, Moh.; Nawawi, M. Syathibi; Irhamni, Irhamni (citeus, 2018)
This research aimed at describing the application of Lesson Study to increase lecturer’s teacing performance in teaching Nahwu. The researchers used classroom action research in two cycles. The subjects of this research were the students taking Nahwu course with low competence. The result showed that the lecturer model was successful to enhance his patience which he did not recognise before to solve his teaching performance of “difficult” course, i.e. discussing the problem with his colleagues. The observer of this Lesson Study scored 95% for the success of applying Lesson Study, and 98% for the positive change of each step done.